A STUDY ON THE ABILITY OF THE SECOND YEAR STUDENTS OF ENGLISH STUDY PROGRAM FKIP UNIVERSITAS RIAU IN LISTENING TO CONVERSATIONS - Riski Mardhatilah; Marzuki '; Eliwarti ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims at finding the ability of the second year students of English Study Program FKIP Univeritas Riau in listening to conversations. The writer used Cluster Random Sampling technique to choose the sample. There are three classes for population of this research consists of 90 students there are class A, B and C, class B was chosen as the sample consisted of 30 students. The instrument of this research was in the form of multiple choices test which consisted of tryout and sample. The test was listening test. The test had four scripts and each script had five questions based on listening question comprehension components, so there were 20 questions for the script. The writer used SPSS 16.0 Program to analyze the data. Based on the results, there are two students in the excellent level (6,7%), and eleven of the students (36, 7%) were at good level, 33,3% were at mediocre level, and 23, 3% was at poor level. So, from the result of the calculation, the majority of student’s ability in listening comprehension on conversation was at good level. The data also indicated that the highest score obtained by students was 85 while the lowest score was 30, and for each classification of question, the mean score of the students’ ability for finding main idea was 65,33 finding detail was 42,00, identifying inference was 66,00 and identifying restatement was 52,00. It means that identifying detail was the students’ lowest score and finding main idea was the students’ highest score of the second year students especially students from class B of English study program FKIP-UR in listening comprehension on conversations.Key Words: Ability,Conversation, Listening Comprehension